Augmented Reality Introduction To Cirebon Mask At Setia Darma Mask House Gianyar - Ariantini, Made Suci; Rajasyah, Alfatino Yohan; Ariasih, Ni Kadek; Indradewi, I Gusti Ayu Agung Diatri; Parwita, Wayan Gede Suka (SEAN Institute, 2024)
This research aims to explore the application of Augmented Reality (AR) technology in the context of introducing Cirebon Masks at the Setia Darma Mask House, Gianyar using Marker Based. Cirebon masks have high cultural and artistic value in traditional Indonesian art, and the Setia Darma Mask House is an important place in introducing and preserving this art to the wider community. Using AR as a tool, this research investigates ways in which this technology can be used to provide visitors with an interactive and immersive learning experience about Cirebon Masks. The research methodology involved developing a custom AR application that allows users to see, hear, and interact with a virtual representation of the Cirebon Mask. Data was collected through observation, interviews and literature study to evaluate the effectiveness of the application. From the test results of 8 tests on the menu in the system using the black box testing method, the system is in accordance with the expected results, namely there are no errors when the system is used. the results of usability testing with the values obtained, namely Application Learnability is 89.4% which means Very Good, Efficiency gets 89.8% which means Very Good, Memorability gets 91.7% which means Very Good, Error gets 63.7% which means Fairly Good and Satisfaction gets 90, 1% which means Very Good